2018
DOI: 10.1073/pnas.1721395115
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the nonlegume Parasponia reveals insights into evolution of nitrogen-fixing rhizobium symbioses

Abstract: SignificanceFixed nitrogen is essential for plant growth. Some plants, such as legumes, can host nitrogen-fixing bacteria within cells in root organs called nodules. Nodules are considered to have evolved in parallel in different lineages, but the genetic changes underlying this evolution remain unknown. Based on gene expression in the nitrogen-fixing nonlegume Parasponia andersonii and the legume Medicago truncatula, we find that nodules in these different lineages may share a single origin. Comparison of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
378
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 220 publications
(395 citation statements)
references
References 103 publications
10
378
1
5
Order By: Relevance
“…Furthermore, it was shown that, in L. japonicus , ectopic expression of LjNF‐YA1 results in lateral roots with malformed tips (Soyano et al ., ; Sorin et al ., ) We observed a mild, though consistent, decrease in lateral roots formed in plantlets containing a mutation in Pannf‐ya1 . This supports the findings that NF‐YA1 orthologous genes have a nonsymbiotic function in root development, and may explain why NF‐YA1 is not pseudogenized in species that have lost the nodulation trait (Soyano et al ., ; Griesmann et al ., ; van Velzen et al ., ). As the P. andersonii nf‐ya1 knockout mutants are not affected in the symbiosis with arbuscular mycorrhiza, it suggests that NF‐YA1 symbiotic functioning is exclusively required to allow entry of symbiotic bacteria.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, it was shown that, in L. japonicus , ectopic expression of LjNF‐YA1 results in lateral roots with malformed tips (Soyano et al ., ; Sorin et al ., ) We observed a mild, though consistent, decrease in lateral roots formed in plantlets containing a mutation in Pannf‐ya1 . This supports the findings that NF‐YA1 orthologous genes have a nonsymbiotic function in root development, and may explain why NF‐YA1 is not pseudogenized in species that have lost the nodulation trait (Soyano et al ., ; Griesmann et al ., ; van Velzen et al ., ). As the P. andersonii nf‐ya1 knockout mutants are not affected in the symbiosis with arbuscular mycorrhiza, it suggests that NF‐YA1 symbiotic functioning is exclusively required to allow entry of symbiotic bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…Protein sequences of L. japonicus (Lj3.0, Lotus Base (REF; Mun et al ., ); Sato et al ., ), Glycine max (Wm82.a2.v1; Sato et al ., ; Schmutz et al ., ), Phaseolus vulgaris (Pvulgaris v.2.1; Schmutz et al ., ), Morus notabilis (Genbank ATGF00000000.1; He et al ., ), Prunus persica (Ppersica v.2.1; International Peach Genome Initiative et al ., ) Fragaria vesca (Fvesca v.1.1; Shulaev et al ., ) were retrieved from P hytozome 12 (http://phytozome.jgi.doe.gov/), unless stated otherwise. Casuarina glauca and Datisca glomerata assemblies were downloaded and set up as custom B last database in Geneious 8.1.9 (Griesmann et al ., ; van Velzen et al ., ). Sequences from diploid Peanut Arachis duranensis were retrieved from NCBI (Bertioli et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations